Difference between revisions of "2015 AIME I Problems/Problem 13"
Channing421 (talk | contribs) (→Solution 6 (EZ)) |
m (→Solution) |
||
Line 2: | Line 2: | ||
With all angles measured in degrees, the product <math>\prod_{k=1}^{45} \csc^2(2k-1)^\circ=m^n</math>, where <math>m</math> and <math>n</math> are integers greater than 1. Find <math>m+n</math>. | With all angles measured in degrees, the product <math>\prod_{k=1}^{45} \csc^2(2k-1)^\circ=m^n</math>, where <math>m</math> and <math>n</math> are integers greater than 1. Find <math>m+n</math>. | ||
− | + | ==Solution 1== | |
− | |||
Let <math>x = \cos 1^\circ + i \sin 1^\circ</math>. Then from the identity | Let <math>x = \cos 1^\circ + i \sin 1^\circ</math>. Then from the identity | ||
<cmath>\sin 1 = \frac{x - \frac{1}{x}}{2i} = \frac{x^2 - 1}{2 i x},</cmath> | <cmath>\sin 1 = \frac{x - \frac{1}{x}}{2i} = \frac{x^2 - 1}{2 i x},</cmath> | ||
Line 15: | Line 14: | ||
It is easy to see that <math>M = 2^{89}</math> and that our answer is <math>2 + 89 = \boxed{91}</math>. | It is easy to see that <math>M = 2^{89}</math> and that our answer is <math>2 + 89 = \boxed{91}</math>. | ||
− | + | ==Solution 2== | |
Let <math>p=\sin1\sin3\sin5...\sin89</math> | Let <math>p=\sin1\sin3\sin5...\sin89</math> | ||
Line 32: | Line 31: | ||
Thus the answer is <math>2+89=\boxed{091}</math> | Thus the answer is <math>2+89=\boxed{091}</math> | ||
− | + | == Solution 3 == | |
Similar to Solution <math>2</math>, so we use <math>\sin{2\theta}=2\sin\theta\cos\theta</math> and we find that: | Similar to Solution <math>2</math>, so we use <math>\sin{2\theta}=2\sin\theta\cos\theta</math> and we find that: | ||
<cmath>\begin{align*}\sin(4)\sin(8)\sin(12)\sin(16)\cdots\sin(84)\sin(88)&=(2\sin(2)\cos(2))(2\sin(4)\cos(4))(2\sin(6)\cos(6))(2\sin(8)\cos(8))\cdots(2\sin(42)\cos(42))(2\sin(44)\cos(44))\\ | <cmath>\begin{align*}\sin(4)\sin(8)\sin(12)\sin(16)\cdots\sin(84)\sin(88)&=(2\sin(2)\cos(2))(2\sin(4)\cos(4))(2\sin(6)\cos(6))(2\sin(8)\cos(8))\cdots(2\sin(42)\cos(42))(2\sin(44)\cos(44))\\ | ||
Line 56: | Line 55: | ||
The answer is therefore <math>m+n=(2)+(89)=\boxed{091}</math>. | The answer is therefore <math>m+n=(2)+(89)=\boxed{091}</math>. | ||
− | + | ==Solution 4== | |
Let <math>p=\prod_{k=1}^{45} \csc^2(2k-1)^\circ</math>. | Let <math>p=\prod_{k=1}^{45} \csc^2(2k-1)^\circ</math>. | ||
Line 70: | Line 69: | ||
Using the fact that <math>\sin\theta=\cos(90^{\circ}-\theta)</math> again, our equation simplifies to <math>\sqrt{\frac{1}{2p}}=\frac{\sin90^\circ}{2^{45}}</math>, and since <math>\sin90^\circ=1</math>, it follows that <math>2p = 2^{90}</math>, which implies <math>p=2^{89}</math>. Thus, <math>m+n=2+89=\boxed{091}</math>. | Using the fact that <math>\sin\theta=\cos(90^{\circ}-\theta)</math> again, our equation simplifies to <math>\sqrt{\frac{1}{2p}}=\frac{\sin90^\circ}{2^{45}}</math>, and since <math>\sin90^\circ=1</math>, it follows that <math>2p = 2^{90}</math>, which implies <math>p=2^{89}</math>. Thus, <math>m+n=2+89=\boxed{091}</math>. | ||
− | + | ==Solution 5== | |
Once we have the tools of complex polynomials there is no need to use the tactical tricks. Everything is so basic (I think). | Once we have the tools of complex polynomials there is no need to use the tactical tricks. Everything is so basic (I think). | ||
Line 87: | Line 86: | ||
<cmath>\prod_{k=1}^{45}\csc^2\frac{(2k-1)\pi}{180} = 2^{89}</cmath> | <cmath>\prod_{k=1}^{45}\csc^2\frac{(2k-1)\pi}{180} = 2^{89}</cmath> | ||
-Mathdummy | -Mathdummy | ||
− | |||
==See Also== | ==See Also== |
Revision as of 12:13, 29 December 2021
Problem
With all angles measured in degrees, the product , where
and
are integers greater than 1. Find
.
Solution 1
Let . Then from the identity
we deduce that (taking absolute values and noticing
)
But because
is the reciprocal of
and because
, if we let our product be
then
because
is positive in the first and second quadrants. Now, notice that
are the roots of
Hence, we can write
, and so
It is easy to see that
and that our answer is
.
Solution 2
Let
because of the identity
we want
Thus the answer is
Solution 3
Similar to Solution , so we use
and we find that:
Now we can cancel the sines of the multiples of
:
So
and we can apply the double-angle formula again:
Of course,
is missing, so we multiply it to both sides:
Now isolate the product of the sines:
And the product of the squares of the cosecants as asked for by the problem is the square of the inverse of this number:
The answer is therefore
.
Solution 4
Let .
Then, .
Since , we can multiply both sides by
to get
.
Using the double-angle identity , we get
.
Note that the right-hand side is equal to , which is equal to
, again, from using our double-angle identity.
Putting this back into our equation and simplifying gives us .
Using the fact that again, our equation simplifies to
, and since
, it follows that
, which implies
. Thus,
.
Solution 5
Once we have the tools of complex polynomials there is no need to use the tactical tricks. Everything is so basic (I think).
Recall that the roots of are
, we have
Let
, and take absolute value of both sides,
or,
Let
be even, then,
so,
Set
and we have
,
-Mathdummy
See Also
2015 AIME I (Problems • Answer Key • Resources) | ||
Preceded by Problem 12 |
Followed by Problem 14 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 | ||
All AIME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.